Health Promotion Activities in Bandung Public Health Centre (Puskesmas) - Nadya, Siti Fairuz; Arya, Insi Farisa Desy; Alam, Anggraini (Althea Medical Journal, 2016)
Background: Health promotion is one of Public Health Centre (Pusat Kesehatan Masyarakat, Puskesmas) essential health effort able to increase community health status. The purpose of this study was to describe health promotion activities in Bandung Public Health Centre (Puskesmas).Methods: This study was a cross sectional descriptive study using questionnaire as data collection instrument. The questionnaires were distributed to 24 Puskesmas in Bandung that were selected randomly using simple random sampling method. The process of questionnaire filling was performed by health promotion officer after informed consent was done. The variables were basic health promotion strategies, health promotion supports, health promotion in health facility and health promotion in community.Results: Most of the Puskesmas showed that basic health promotion strategies, health promotion in health facility and health promotion in community were already done. Support media that was mostly used was printed media while lectures was the most used method. Human resources practitioner and coordinator of health promotion were dominated by mid level health workers consists of midwife and nurse. This study showed that the majority of health promotion coordinator had underwint training and certificate related to health promotion. The availability of funds were possessed by 13 out of 24 sample. While, health promotion guideline were possessed by less than half of the sample.Conclusions: Health promotion is done in almost all sample. There is lack of health promotion support in the form of the availability of funds and guideline of health promotion method. [AMJ.2016;3(3):459â67]DOI: 10.15850/amj.v3n3.864